Belleza Sdn. Bhd (Combae) / Nurul Nabila Meskam - Meskam, Nurul Nabila (2020)
Belleza Sdn. Bhd is producing a new product to the customers which is multifunction comb that known as Combae. Combae is 3-in-1 hair styling tools which have functioning of hair product application, hair straightener and combing. We also provide capsule containing hair product. It has its own uniqueness that making it different from other product. There are certain group of people who have busy lifestyles like travellers and business person, which needed shorter time in grooming their hair. So, our product is the perfect comb for them as it has special features which they can groom their hair quick and still can achieve their desired hairstyle. Our company focuses on producing a comb that could shorten the time for grooming hair so our customer can optimize their time management. Our product also has special features of extendable and ergonomically handle which is an ideal comb for the arthritis patient. So, they can groom the hair easily and do not need much effort. Overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain and the channel of distribution in the target market.